Inhibition of M/Kv7 Currents Contributes to Chloroquine-Induced Itch in Mice - Zhang, Dong; Men, Hongchao; Zhang, Ludi; Gao, Xiangxin; Wang, Jingjing; Li, Leying; Zhu, Qiaoying; Zhang, Hailin; Jia, Zhanfeng (Frontiers in Molecular Neuroscience, 2020)
M/Kv7 potassium channels play a key role in regulation of neuronal excitability. Modulation of neuronal excitability of primary sensory neurons determines the itch sensation induced by a variety of itch-causing substances including chloroquine (CQ). In the present study, we demonstrate that suppression of M/Kv7 channel activity contributes to generation of itch in mice. CQ enhances excitability of the primary sensory neurons through inhibiting M/Kv7 potassium currents in a Ca2+ influx-dependent manner. Specific M/Kv7 channel opener retigabine (RTG) or tannic acid (TA) not only reverses the CQ-induced enhancement of neuronal excitability but also suppresses the CQ-induced itch behavior. Systemic application of RTG or TA also significantly inhibits the itch behavior induced by a variety of pruritogens. Taken together, our findings provide novel insight into the molecular basis of CQ-induced itch sensation in mammals that can be applied to the development of strategies to mitigate itch behavior.